Enhancing Arabic Vocabulary Mastery Through Communicative Strategies: Evidence from Malaysia - Hanifansyah, Nur; Mahmudah, Menik (Institut Agama Islam Negeri Palangka Raya, 2024)
This research aims to improve the mastery of Arabic vocabulary at Maktab Mahmud Yan, Kedah, Malaysia. In this study, the researcher employed a descriptive qualitative method. As a sample for this research, the researcher selected level 4, equivalent to the second grade of Madrasah Aliyah. The findings of this research revealed that some students encountered issues in learning Arabic. The problems faced by the students were both linguistic and non-linguistic in nature. Therefore, the researcher implemented a communicative approach strategy to support the improvement of Arabic language learning. After applying this communicative approach strategy, there was a proven increase in student learning outcomes. The communicative approach strategy helped students enhance their ability to speak in Arabic. Students were also able to express themselves, share opinions, and be more active in asking questions in Arabic.